2020
DOI: 10.1158/1078-0432.ccr-20-0834
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Syndrome with Ivosidenib and Enasidenib Treatment in Patients with Relapsed or Refractory IDH-Mutated AML: A U.S. Food and Drug Administration Systematic Analysis

Abstract: Purpose: Differentiation syndrome (DS) is a serious adverse reaction of isocitrate dehydrogenase (IDH) inhibitors ivosidenib and enasidenib in patients with (IDH)1-and IDH2-mutated acute myeloid leukemia (AML), respectively.Experimental Design: During FDA review of marketing applications for ivosidenib and enasidenib, data from pivotal trials were queried to identify cases of DS in patients with relapsed or refractory (R/R) AML. One hundred seventy-nine patients with R/R AML received ivosidenib and 214 receive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 27 publications
2
97
0
Order By: Relevance
“… 23 , 29 , 41 In contrast to a rapid occurrence of DS in APL (median of 12 days), 38 , 42 , 43 the onset of DS was delayed in patients treated with IDH inhibitors. 23 , 40 , 41 A recent comprehensive analysis concluded that the incidence of DS in IDH inhibitor-treated patients (19%) 40 is similar to the rate observed for ATRA-treated APL ( ∼ 25%). 39 , 42 , 43 This necessitates routine monitoring for DS in patients on IDH inhibitor therapy.…”
Section: Newly-approved Targeted Therapies For Acute Myeloid Leukemiamentioning
confidence: 76%
See 1 more Smart Citation
“… 23 , 29 , 41 In contrast to a rapid occurrence of DS in APL (median of 12 days), 38 , 42 , 43 the onset of DS was delayed in patients treated with IDH inhibitors. 23 , 40 , 41 A recent comprehensive analysis concluded that the incidence of DS in IDH inhibitor-treated patients (19%) 40 is similar to the rate observed for ATRA-treated APL ( ∼ 25%). 39 , 42 , 43 This necessitates routine monitoring for DS in patients on IDH inhibitor therapy.…”
Section: Newly-approved Targeted Therapies For Acute Myeloid Leukemiamentioning
confidence: 76%
“…The most common clinical features of IDH-DS were dyspnea and pulmonary infiltrates or pleuropericardial effusion, while hypotension was the least common symptom. 40 IDH-DS was effectively managed by dose interruption and treatment with glucocorticoids and hydroxyurea. 23 , 29 , 41 In contrast to a rapid occurrence of DS in APL (median of 12 days), 38 , 42 , 43 the onset of DS was delayed in patients treated with IDH inhibitors.…”
Section: Newly-approved Targeted Therapies For Acute Myeloid Leukemiamentioning
confidence: 99%
“…What might further contribute to a lower DS incidence in IDH-inhibitors and retinoic acid derivatives is that three of the four clinical trials were phase 1 and using dose escalation, meaning that part of the patients received very low doses of the differentiating drugs. Since our estimates of the incidence of DS in the treatment with the IDH-inhibitors, ivosidenib and enasidenib, is based on the published phase 1/2 clinical trials, we may be underestimating the real-world incidence and mortality of DS associated with IDH-inhibitors [ 13 , 14 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the delayed time to onset observed in the IDH-inhibitors indicates that either DS develops later in these patients, or there was a delay in clinical detection. A recent systematic analysis by the US FDA conducted an algorithmic analysis to improve the capture of DS cases in patients using IDH-inhibitors as many of the signs and symptoms of DS may not be initially recognized [ 14 ]. The authors concluded that DS was likely common with the IDH-inhibitors, and increased awareness of the early signs and symptoms is needed to decrease the potential for severe or fatal complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation